Caviar of the east - Mohd Ghazali, Hasanah; Abdul Karim, Muhammad Shahrim; Abu Bakar, Ainul Zakiah (Universiti Putra Malaysia Press, 2015)
Edible bird’s nest ‘yan wo’ has been referred to as the ‘Caviar of the East’. Like caviar, the salt-cured eggs of sturgeons, the edible bird’s nest is expensive and prized as a delicacy, but more than caviar, it is also highly regarded as a health food. Premium nests come from Malaysia, Thailand, and Vietnam. The edible bird’s nests are essentially constructed from the salivary secretion of swiftlets, small birds that usually dwell in caves.